Can we have a second light Higgs boson in the \(U(1)\) model? - Do, Thi Huong; Nguyen Tuan, Duy (Communications in Physics, 2025)
Our theoretical model predicts the existence of a light-mass CP-even Higgs boson (\(H_1\)) and a light-mass pseudo-scalar boson (\(A\)). The mass ranges for these particles are determined by the cubic coupling, \(μ_4\), at the electroweak energy scale. These light Higgs bosons can produce flavor-changing neutral currents, which play a significant role in meson mixing processes. Specifically, when \(m_A = s_α m_H_1\), the contributions to flavor mixing can either completely cancel each other out or, conversely, become extremely large.